2015
DOI: 10.1136/bjophthalmol-2014-306543
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double-masked, controlled study of the efficacy and safety of intravitreal bevacizumab versus ranibizumab in the treatment of macular oedema due to branch retinal vein occlusion: MARVEL Report No. 1

Abstract: http://www.ctri.nic.in/ CTRI/2012/01/003120.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 20 publications
1
80
0
1
Order By: Relevance
“…From a functional point of view, the percentage of patients with CRVO and visual loss greater than 15 letters has been noted in 5% of the patients after treatment by aflibercept [31], 6% for bevacizumab [32] and 3-12% for ranibizumab [33,34]. Failure has also been reported in cases when rescue laser treatment was prescribed in BRVO patients for persistent diffuse oedema in 10% of the ranibizumab group and 21% of the bevacizumab group in the MARVEL study [35] and in 20% after ranibizumab [34]. Recalcitrant ME in patients treated with anti-VEGF has been previously associated with systemic hypertension and more retinal ischaemia [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…From a functional point of view, the percentage of patients with CRVO and visual loss greater than 15 letters has been noted in 5% of the patients after treatment by aflibercept [31], 6% for bevacizumab [32] and 3-12% for ranibizumab [33,34]. Failure has also been reported in cases when rescue laser treatment was prescribed in BRVO patients for persistent diffuse oedema in 10% of the ranibizumab group and 21% of the bevacizumab group in the MARVEL study [35] and in 20% after ranibizumab [34]. Recalcitrant ME in patients treated with anti-VEGF has been previously associated with systemic hypertension and more retinal ischaemia [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Using a fixed dosing regimen of monthly injections for a set period, all studies demonstrated aflibercept and ranibizumab as effective treatments for macular oedema from BRVO and CRVO respectively with low local and systemic safety issues identified. Clinical studies have further shown anti-VEGF agent bevacizumab to be of similar efficacy in reducing macular thickness and improving visual acuity (VA) 2 9…”
Section: Introductionmentioning
confidence: 99%
“…Ranibizumab is a recombinant humanized monoclonal antibody fragment. Clinically it was demonstrated to alleviate macular edema, and reduce neovascularization and vascular leakage in patients by effectively antagonizing VEGF (13,14). In this study, the levels of VEGF in rat serum and aqueous humor were determined, and it was found that the VEGF levels of rats treated with ranibizumab were significantly lower (P<0.05) than those of the control group, and decreased further over time in the treatment.…”
Section: Discussionmentioning
confidence: 99%